The new challenge in automation pilotage system for stringent port navigation - Mahmud, Razali; Ghazali, Noorzalianee (2006)
This study is part of the research on integrated port database system that was developed to deal with the inefficiency issues cause from the overlapping task by multi-agency in port area. These agencies carried out several parallel activities in the port area. The main challenge of the study is to ensure the safety of the ships as well as the passenger due to these parallel activities. The regulation that has been set up to overcome the problem sometimes could lead to inefficiency of the port activities such as the delay of departure as well as the berthing. Thus the alternative approach has been tested to overcome the problem. Automation pilotage is one of the approaches that successfully meet the challenge to overcome the problem of pilot incapability to navigate in port area. Current regulation that requires local port pilot to berthing the visiting ship need to be revised sooner as the new alternative of automation berthing system are ready to compete.